2007
DOI: 10.1103/physrevd.76.081701
|View full text |Cite
|
Sign up to set email alerts
|

General very special relativity is Finsler geometry

Abstract: We ask whether Cohen and Glashow's very special relativity model for Lorentz violation might be modified, perhaps by quantum corrections, possibly producing a curved space-time with a cosmological constant. We show that its symmetry group ISIM(2) does admit a 2-parameter family of continuous deformations, but none of these give rise to noncommutative translations analogous to those of the de Sitter deformation of the Poincaré group: space-time remains flat. Only a 1-parameter family DISIM b 2 of deformations o… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
373
0

Year Published

2009
2009
2021
2021

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 256 publications
(374 citation statements)
references
References 16 publications
1
373
0
Order By: Relevance
“…[30,21,22,37,29], we concluded that classical and quantum gravity models on (co) tangent bundles positively result in generalized Finsler like theories with violation of local Lorentz symmetry. The conclusion was supported also by a series of works on definition of spinors and field interactions on (in general, higher order) locally anisotropic spacetimes [38,39], on low energy limits of (super) string theory [40,41,42] and possible Finsler like phenomenological implications and symmetry restriction of quantum gravity [43,44,45]. Here, we emphasize that the nonholonomic quantum deformation formalism can be re-defined for nonholonomic (pseudo) Riemannian, or Riemann-Cartan, manifolds with fibred structure.…”
Section: Introductionmentioning
confidence: 81%
See 2 more Smart Citations
“…[30,21,22,37,29], we concluded that classical and quantum gravity models on (co) tangent bundles positively result in generalized Finsler like theories with violation of local Lorentz symmetry. The conclusion was supported also by a series of works on definition of spinors and field interactions on (in general, higher order) locally anisotropic spacetimes [38,39], on low energy limits of (super) string theory [40,41,42] and possible Finsler like phenomenological implications and symmetry restriction of quantum gravity [43,44,45]. Here, we emphasize that the nonholonomic quantum deformation formalism can be re-defined for nonholonomic (pseudo) Riemannian, or Riemann-Cartan, manifolds with fibred structure.…”
Section: Introductionmentioning
confidence: 81%
“…The solutions for the "cotangent" gravity are, in general, with violation of Lorentz symmetry induced by quantum corrections. The nature of such quantum gravity corrections is different from those defined by FinslerLagrange models on tangent bundle (see, for instance, [33,34,43,44,45])), locally anisotropic string gravity [40,41,42] with corrections from extradimensions and nonholonomic spinor gravity [37,38,39] and noncommutative gravity, see reviews of results in [29,30]. The aim of this section is to analyze how a generalization of Einstein gravity can be performed on cotangent bundles in terms of canonical * φ-connections, with geometric structures induced by an effective Hamiltonian fundamental function, when the Fedosov quantization can be naturally performed.…”
Section: Quantum Gravitational Field Equationsmentioning
confidence: 99%
See 1 more Smart Citation
“…The above described procedure leads to breaking of the principle of relativity, but one may wonder if other possibilities exist that violate Lorentz invariance but preserve the principle of relativity. One such possibility is represented by the very special relativity framework [14], which corresponds to the break down of isotropy and is described by a Finslerian-type geometry [15,16,17]. In this example, however, the new relativity group generators number less than the ten generators associated with Poincaré invariance.…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, in the framework of Finsler geometry and as in modified theories of gravity (MOND etc…), the flat rotation curves of spiral galaxies can be deduced naturally without involving dark matter. This has led to a theoretical interest a specially in the so called a Randers-Finsler space of approximate Bewald type where a modified Friedmann model is proposed [23]- [26]. It is shown that the accelerated expanding universe is guaranteed by a constrained Randers-Finsler structure without invoking dark energy and the additional term in the geodesic equation acts as a repulsive force against the gravity.…”
Section: Introductionmentioning
confidence: 99%